Fabrication and characterization of electrospun bionanocomposites of poly (vinyl alcohol)/nanohydroxyapatite/cellulose nanofibers. Issue 13 (1st September 2016) - Enayati, Mohammad Saied; Behzad, T.; Sajkiewicz, P.; Bagheri, R.; Ghasemi-Mobarakeh, L.; Kuśnieruk, S.; Rogowska-Tylman, J.; Pahlevanneshan, Z.; Choińska, E.; Święszkowski, W.
ABSTRACT: The aim of the present study was preparation, optimization, and systematic characterization of electrospun bionanocomposite fibers based on polyvinyl alcohol (PVA) as matrix and nanohydroxy apatite (nHAp) and cellulose nanofibers (CNF) as nanoreinforcements. The presence of nHAp and nHAp-CNF affected the morphology of electrospun mats and reduced fiber diameter, particularly at a higher content of nanofillers. The obtained results of FTIR, DSC, and WAXS proved the crystallinity reduction of electrospun nancomposites. Both nHAp and nHAp-CNF addition led to a significant increase of Young modulus with the highest stiffness for nanocomposite fibers at 10 wt% of nHAp and 3 wt% of CNF. GRAPHICAL ABSTRACT: